Validation of a minimally-invasive method for sampling epithelial-associated microorganisms on the rumen wall - Henniger, Madison T.; Rowan, Troy N.; Beever, Jonathan E.; Mulon, Pierre-Yves; Smith, Joe S.; Voy, Brynn H.; Wells, Jim E.; Kuehn, Larry A.; Myer, Phillip R. (Frontiers in Animal Science, 2023)
The rumen microbiome provides approximately 70% of the required energy for the host by converting low-quality feedstuffs into usable energy for ruminants. The energy produced by the microorganisms is subsequently absorbed through the rumen epithelium and used towards growth and energy maintenance. There is evidence that ruminal epimural microbes directly interact with the rumen epithelium, acting as an intermediary communicator between the rumen liquid fraction and the host. Epimural microbiota have been demonstrated to be distinct from the ruminal liquid microbiome and perform unique roles within the rumen environment. However, methods to sample epimural communities from the rumen wall are limited and typically invasive, requiring animal fistulation or harvesting. To characterize the epimural communities present on the rumen wall, a novel and minimally-invasive surgical method was developed to swab the epithelium of the ventral sac of the rumen. The objective of this study was to validate this sampling method by comparing epimural and liquid fraction bacterial communities. During a 70-day feeding trial, Angus steers (n=45) were sampled on day 35 using the novel surgery method and tubed on day 70 to sample rumen liquid content. Genomic DNA was used to generate amplicon libraries of the V4 region of the 16S rRNA gene. There were no differences between alpha diversity indices when comparing rumen versus epimural bacterial communities (P>0.05). The Bray-Curtis dissimilarity was used to ordinate ASV counts, and then tested for differences between rumen and epimural communities using a PERMANOVA with 999 permutations (P < 0.05). Differential abundances of bacterial communities were tested using ANCOM-BC and MaAsLin2, where significance was determined by Q<0.05 and overlap between both analysis methods. Within the 91 taxa that differed in abundance, 451 ASVs were found to be different between sample types (Q < 0.05). Unique ASVs associated with Prevotella, Succinivibrio, family-level Eubacterium, and family-level Succinivibrio were in greater abundance for the rumen epithelial-associated bacterial communities (Q < 0.05). The results demonstrate that the novel method of sampling from the rumen wall can capture differences between epimural and ruminal fluid bacterial communities, thus facilitating studies investigating the interactions between epimural bacteria with the host.